Modifikasi Vigenere Cipher Dengan Pembangkit Kunci Blum Blum Shub - Firman Telaumbanua; Taronisokhi Zebua (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2020)
Vigenere cipher is a symmetric key algorithm that uses alphabetic substitution by using these letters as plaintext and key letters that have comparable positions. Along with the development of human science, the weaknesses of the vigenere cipher were discovered. One way that can be done to overcome the weaknesses of the vigenere cipher above is to generate a more random key. This study describes how the procedure is carried out to modify the key generation used in the vigenere cipher algorithm. The key generation process is carried out based on the blum blum shub key generator, meaning that the key used in the encryption and decryption process is the key generated based on the blum blum shub key generator, so that the modification process carried out in generating the key can minimize key-breaking actions by other parties as well as This algorithm can be more optimal in securing data. The result of this research is to design an android-based data security application using the modified vigenere cipher method using the blum blum shub key generator. This application can be used to secure text data, so that it cannot be retrieved by other people. In addition, the application to be designed is easier to use in data security.Keywords: Security, Keys, Algorithm, Cryptography, Blum Blum Shup